Parameter Optimization and Experimental Verification of V-belt CVT based on Genetic Algorithm - Tian Zhewen; Zuo Xiaochao; Li Xiaoning (Jixie chuandong)
In order to make the V-belt CVT match the Racing Baja condition and engine characteristics， its key parameters are optimized. A V-belt CVT mechanical model is established， and the CVT speed regulation characteristics are analyzed and simulated in Matlab. The genetic algorithm is used to optimize the key parameters of CVT with the aim of improving the power. The bench is set up for test verification. The test results show that the simulation results are basically consistent with the test data. The CVT transmission ratio changes according to the actual working conditions， and the engine always works in the peak torque and power corresponding speed range (2 800 ~3 600 r/min)， and the vehicle power performance is significantly improved. This study has a certain guiding role in the parameter matching and optimization of V-belt CVT.